2013
DOI: 10.1021/jf4009313
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pseudomonas aeruginosa and Escherichia coli O157:H7 Biofilm Formation by Plant Metabolite ε-Viniferin

Abstract: Pathogenic biofilms are associated with persistent infection due to their high resistances to diverse antibiotics. Pseudomonas aeruginosa infects plants, animals, and humans and is a major cause of nosocomial diseases in patients with cystic fibrosis. In the present study, the antibiofilm abilities of 522 plant extracts against P. aeruginosa PA14 were examined. Three Carex plant extracts at a concentration of 200 μg/mL inhibited P. aeruginosa biofilm formation by >80% without affecting planktonic cell growth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 43 publications
3
50
0
1
Order By: Relevance
“…Similar effects were reported by Cho et al. () evaluating some flavonoids on BF by P. aeruginosa PA14. Plyuta et al.…”
Section: Resultssupporting
confidence: 89%
“…Similar effects were reported by Cho et al. () evaluating some flavonoids on BF by P. aeruginosa PA14. Plyuta et al.…”
Section: Resultssupporting
confidence: 89%
“…EHEC strains contain a series of fimbriae such as curli fimbriae (Csg), type I fimbriae (Fim), E. coli common pilus (Ecp), F9 fimbriae (Z2200), and other fimbrial proteins29. It has been also reported that several phytochemicals, such as, 3-indolylacetonitrile30, phloretin31, resveratrol (and its dimer viniferin)3233, cinnamaldehyde18, coumarin34, and ginkgolic acids17 inhibit EHEC biofilm formation primarily by inhibiting curli fimbriae production. Hence, it appears that fimbriae-reducing ability is not rare in the plant kingdom and that the fimbriae inhibition could be viewed a practical target for suppressing EHEC biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Carex plant extracts inhibited E. coli O157:H7 and Pseudomonas aeruginosa biofilm formation without affecting planktonic cells growth. One of the active antibiofilm compounds in these extracts was ε‐viniferin (Cho et al ., ). Plant sterols such as the β‐sitosterol glucoside from citrus are potent inhibitors of E. coli O157:H7 biofilm formation and motility, without affecting the cell viability.…”
Section: The Plant Response and Its Effect On Bacterial Biofilmsmentioning
confidence: 97%